(untitled) (Nóema, 2015)
The personality of Shitao (1642-1707), Chinese painter active during the beginning of Qing dynasty, deserves to be figured out by the comparison of his own particular life, his artistic work, – above all in the phase of its full utterance, – and the philosophical thoughts that he has revealed in his Dialogues on painting. By the union of all these features, Shitao has laid down a link between the «one-brushstroke» and the holistic fusion of his Spirit with Nature.